A dynamic systems approach to personality: The Personality Dynamics (PersDyn) model. (1st July 2019) - Sosnowska, Joanna; Kuppens, Peter; De Fruyt, Filip; Hofmans, Joeri
Abstract: In the present paper, we offer an integrative approach to personality that combines within-person and between-person differences. By drawing on the principles of dynamic systems theory, we present Personality Dynamics model – a novel framework that captures people's typical pattern of changes in personality states using three model parameters: baseline personality, reflecting the stable set point around which one's states fluctuate, personality variability, or the extent to which one's personality states fluctuate across time and situations, and personality attractor force, pertaining to the swiftness with which deviations of one's baseline are pulled back to the baseline. We argue that the dynamic approach to personality represented in the PersDyn model has the potential to integrate different perspectives on individual differences. We also demonstrate that the dynamic approach to personality offers a consensual paradigm of personality with the potential to advance our understanding and knowledge of individual differences, by detailing the factors and processes included in the model, as well as links to existing theories and applications in various research lines.